Competition and market strategies in the Swiss fixed telephony market - Roberto E. Balmer (International Telecommunications Society (ITS), 2015)
Fixed telephony has long been a fundamentally important market for European telecommunications operators. The liberalisation and the introduction of regulation in the end of the 1990s, however, allowed new entrants to compete with incumbents at the retail level. A rapid price decline and a decline in revenues followed. Increased retail competition eventually led a number of national regulators to deregulate this market. In 2013, however, many European countries (including Switzerland) continued to have partially binding retail price regulation in this market. More than a decade after liberalisation and the introduction of wholesale and retail price regulation, sufficient data is available to empirically measure the success of regulation and assess its continued necessity. This paper develops a market model based on a generalised version of the traditional dominant firm – competitive fringe model allowing for the incumbent a more competitive conduct than that of a dominant firm. A system of simultaneous equations is developed and direct estimation of the incumbent's residual demand function is performed by instrumenting the market price by incumbent-specific cost shifting variables as well as other variables. Unlike earlier papers that assess market power in this market, this paper also adjusts the market model to ensure a sufficient level of cointegration and avoid spurious regression results. This necessitates the introduction of intertemporal effects. While the incumbent's conduct cannot be directly estimated using this framework, the concrete estimates show that its residual demand is inelastic (long run price elasticity of residual demand of -0.12). Such a level of elasticity is shown to be only compatible with a profit maximising incumbent in the case of largely competitive conduct (conduct parameter below 0.12 and therefore close to zero). It is consequently found that the Swiss incumbent acted rather competitively in the fixed telephony retail market in the period under review (2004-2012) and that the (partial) retail price caps in place can no longer be justified on the basis of a lack of competition.
Keywords: 330; residual demand estimation; competition; conduct; time series; dynamic residual demand estimation; fixed voice; fixed telephony; retail market; telecommunications